Upgrade of the thermal power plant flexibility by the steam accumulator. (1st November 2020) - Stevanovic, Vladimir D.; Petrovic, Milan M.; Milivojevic, Sanja; Ilic, Milica
Highlights: Steam accumulator storage provides primary and secondary power control. Accumulated steam replaces turbine extractions for two condensate heaters. Steam discharge from 600 m 3 accumulator provides 27.3 MWe for 27 min. Additional 11.5 MWe power increase is available for 13 min. Control reserve by fresh steam throttling reduces by 4.2% of 650 MWe nominal power. Abstract: Thermal power plants are forced to operate under frequent load changes in energy systems with increased share of solar and wind power plants. These load changes increase thermal power plant aging and reduce their efficiency. Therefore, solutions for energy storage are sought in order to accumulate energy in periods of lower power demand and produce excess power in periods of increased demands. In the present paper the steam accumulator as the thermal energy storage device is applied in a 650 MWe coal-fired thermal power plant to increase its flexibility under the demand for the variable load changes. The steam accumulator is charged during periods of lower power demand, as during the night hours, and discharged during peak load demands. The steam accumulator with volume of 600 m 3 is charged with superheated steam (pressure 4.5 MPa and temperature 335 °C) extracted from the exit of high pressure steam turbine. The steam discharged from the steam accumulator replaces the turbine steam extraction for two low pressure heaters: a 59.5 MWt and a 54.6 MWt heater operating at 0.56 MPa and 0.23 MPa steam pressure. This replacement results in an increase of the steam flow rate through the turbine and the turbine power gain of 27.3 MWe during 27 min and 11.5 MWe for additional 13 min. The proposed solution of the steam accumulator installation in the power plant is a new design. The upgrade of power plant flexibility by steam accumulator is demonstrated.